Surface vector fields estimation using soft computing and remote sensing data at an open water marine renewable test site. (February 2020) - Ren, Lei; Miao, Jianming; Hartnett, Michael
Abstract: Galway Bay has one of the world's few open water marine renewable test sites and so is of national and international interest. A high frequency radar system has been deployed in Galway Bay area to monitor near real time surface currents and waves since July 2011. In this research, a soft computing approach was applied to estimate surface vector fields using the observed radar data. Results indicate that soft computing is a novel and promising method to estimate surface vector fields. It provides a potential way to obtain useful information of coastal water body for marine renewable energy development and assessment.